DOP073 Results of the sixth ECCO Scientific Workshop: The pathogenesis of inflammatory extraintestinal manifestations of inflammatory bowel disease: implications for research, diagnosis, and therapy. (16th January 2018) - Hedin, C R H; Vavricka, S R; Stagg, A J; Schoepfer, A; Raine, T; Puig, L; Pleyer, U; Navarini, A; van der Meulen - de Jong, A E; Maul, J; Katsanos, K H; Kagramanova, A; et al.
Abstract: Background: Approximately 50% of inflammatory bowel disease (IBD) patients experience at least one extraintestinal manifestation (EIM) during their disease course. The pathogenic mechanisms that cause EIM are incompletely understood, however unravelling these pathways has the potential to enhance our understanding of the pathogenesis of IBD overall and improve patient care. Methods: The workshop comprised gastroenterologists of ECCO as well as experts from rheumatology, ophthalmology and dermatology. One group critically appraised the scientific evidence supporting a range of proposed pathogenic mechanisms of EIM, whilst the second group defined strategies and clinical tools that could be employed in future research in EIM. Unanswered questions in the field of EIM were identified. Results: In order to facilitate systematic inclusion of patients in scientific and clinical studies and to align outcome measures across studies, research evaluating EIM needs to be underpinned by widely agreed definitions of the pathology being studied. However, such clear criteria are often lacking in EIM. We considered the evidence supporting the role of the gut microbiota and genotype in EIM pathogenesis as well as the differential therapeutic efficacy of drugs in IBD and EIMs, which may reveal pathogenic mechanisms. We defined two broad groups of speculative immune pathways: 1. Extension of immune responses from the intestine and 2. EIM as independent, but associated inflammatory events. The adequacy of the currently available animal models for the investigation of pathogenic mechanisms in EIM was appraised. The biomarkers and clinical and patient-reported outcome measures currently available to assess inflammation in different somatic systems were compared and suggestions made for future clinical and research use. Conclusions: There is an urgent need to increase understanding of pathogenesis of EIM both to identify new molecular treatment targets, as well as to enhance the strategic application of the currently available drugs according to the character and somatic distribution of inflammation in individual patients. New knowledge challenges traditional organ-based paradigms and we predict that consideration of the total inflammatory burden will drive treatment decisions and define clinical and research outcomes in the future. Many currently available clinical and patient-reported outcome measures are organ-based; therefore novel tools for diagnosis and monitoring of inflammation are needed.